2023
DOI: 10.1158/1078-0432.ccr-23-0006
|View full text |Cite
|
Sign up to set email alerts
|

Collagen-Anchored Interleukin-2 and Interleukin-12 Safely Reprogram the Tumor Microenvironment in Canine Soft-Tissue Sarcomas

Abstract: Purpose: Cytokine therapies such as IL2 and IL12 suffer from impractically small therapeutic windows driven by their on-target, off-tumor activity, limiting their clinical potential despite potent antitumor effects. We previously engineered cytokines that bind and anchor to tumor collagen following intratumoral injection, and sought to test their safety and biomarker activity in spontaneous canine soft-tissue sarcomas (STS). Experimental Desig… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 85 publications
4
11
0
Order By: Relevance
“…To this end, we are interested in evaluating the combination of checkpoint inhibitors with the RT plus intratumoral cytokine treatment in future studies. Our prior work with canine soft tissue sarcomas indicated that checkpoint blockade might relieve counter-regulatory responses to intratumoral cytokine therapy, which we confirmed in the murine B16F10 tumor model 50 .…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…To this end, we are interested in evaluating the combination of checkpoint inhibitors with the RT plus intratumoral cytokine treatment in future studies. Our prior work with canine soft tissue sarcomas indicated that checkpoint blockade might relieve counter-regulatory responses to intratumoral cytokine therapy, which we confirmed in the murine B16F10 tumor model 50 .…”
Section: Discussionsupporting
confidence: 71%
“…Similar to the pivotal Phase III clinical trials with T-VEC 77 , out of concern that longitudinal sampling of the primary treated tumors could confound results by introducing additional paths for intratumoral dose egress, we did not profile the immune response to therapy during treatment. However, building upon our prior characterization of the immune-mediated response to collagen-anchored cytokines in canine soft tissue sarcoma and murine tumors 35,50 , we highlight an anecdotal case of long-term anti-tumor response after the completion of treatment in oral melanoma which presumably involved immune activity.…”
Section: Tumor-localized Il-2/il-12 With Rt Potentiates Responses At ...mentioning
confidence: 89%
See 1 more Smart Citation
“…reported on the use of a collagen-binding cytokine regimen in pet dogs with spontaneously occurring soft-tissue sarcomas. 118 The intratumorally dosed cytokines were reported to be well tolerated with promising biomarker activity as shown by increased T cell infiltration and gene expression programs associated with a strong anti-tumor response.…”
Section: Extracellular Matrix (Ecm) Anchoringmentioning
confidence: 99%
“…In comparison to syngeneic mouse tumors, which often grow and vascularize much more rapidly than human tumors, canine tumors mirror human cancers more faithfully. 118,145 Thus, they may serve as an effective bridge between murine preclinical studies and first-in-human studies.…”
Section: Con Clus I On S and In S I G Htsmentioning
confidence: 99%